Reusing dental implants?: an experimental study for detecting the success rates of re-osseointegration - Murat Ulu; Erdem Kılıç; Emrah Soylu; Mehmet Kürkçü; Alper Alkan (SpringerOpen, 2018)
Abstract Background The aim of this study was to histomorphometrically compare the implant-host integration between retrieved implants and new implants. Methods Jaws in 10 male beagle dogs were divided into four groups, and 36 dental implants were inserted into the jaws. In groups 1 and 2, experimental peri-implantitis was induced within 2 months after implant insertion. In group 1, surface decontamination of implants was achieved using air-flow and citric acid. In group 2, implants were sterilized with autoclave after air-flow and citric acid surface decontamination. Subsequently, these implants were inserted in contralateral jaws of the same dogs and a 3-month period was allowed for osseointegration. In group 3, the implants were removed from human jaws due to peri-implantitis and were inserted into dog jaws following surface cleaning protocol and sterilization with autoclave and a 3-month period was allowed for osseointegration. Group 4 was set as the control group. After the osseointegration period, all the animals were sacrificed. The degree of osseointegration in all groups was evaluated by evaluating the ISQ values and by using histomorphometric measurements. Results Histological findings showed that bone-implant contact (BIC) percentage (mean ± SD) was 83.39% ± 6.37 in group 1, 79.93% ± 11.83 in group 2, 75.45% ± 9.09 in group 3, and 80.53 ± 5.22 in group 4. Moreover, the resonance frequency analysis (RFA) and ISQ values were similar in all four groups both before and after the implantation. Conclusions The results of this experimental study indicated that there is no significant difference between new dental implants and re-used dental implants with regards to osseointegration around the implant.